2023
DOI: 10.1186/s12889-023-15171-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine uptake and hesitation among men and women preparing for pregnancy: a cross-section survey based on the theory of planned behavior

Abstract: Background Given the accelerated speed of COVID-19 vaccine research and administration, the main barriers to herd immunity appear to be concerns about safety and efficacy. Men and women preparing for pregnancy may have the same concerns about COVID-19 vaccination, but few studies have focused on COVID-19 vaccine uptake and hesitation among them. Methods A cross-sectional study was conducted among men and women who were preparing for pregnancy in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For example, two different studies from Malaysia reported vaccination acceptance/intention rates as 64.5% and 83.3% [10,11]. Similarly, four studies from China reported rates of 84.4%, 53.89%, 64.01% and 89.4% [12][13][14][15]. Researchers utilized various techniques such as binary logistic regression and bivariate analysis to identify determinants of vaccine acceptance or intention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, two different studies from Malaysia reported vaccination acceptance/intention rates as 64.5% and 83.3% [10,11]. Similarly, four studies from China reported rates of 84.4%, 53.89%, 64.01% and 89.4% [12][13][14][15]. Researchers utilized various techniques such as binary logistic regression and bivariate analysis to identify determinants of vaccine acceptance or intention.…”
Section: Resultsmentioning
confidence: 99%
“…Pro-vaccine and anti-vaccine attitudes also seemed to play a role. Individuals with a history of getting other vaccines, such as the influenza vaccine, seemed to be more willing to get the COVID-19 vaccine [13,33].…”
Section: Alphonsusmentioning
confidence: 99%